O13 Working definition of gastrointestinal dystonia of severe neuro-disability; outcome of the BSPGHAN/BAPM/BAPS/APPM/BPNA appropriateness panel. (12th September 2022) - Barclay, Andrew; Meade, Susanna; Richards, Catherine; Warlow, Timothy; Lumsden, Daniel; Fairhurst, Charlie; Paxton, Catherine; Forrest, Katharine; Mordekar, Santosh; Campbell, David; Thomas, Julian; Brooks, Michelle; et al.
Abstract : Background and Aims: Children and young people with severe neurosdisabling conditions (CYPWSND) experience an array of serious gastrointestinal symptoms beyond gastro-oesophageal reflux, constipation or dependence on artificial nutrition. When enteral feeds leads to disabling dystonia the term 'gastrointestinal dystonia of severe neurodisability' (GID) has been applied by clinicians. However a clear definition with criteria for entry point is lacking in the literature. We describe the methods for formal establishment of an agreed definition of GID. Methods: After commissioning by BSPGHAN, systematic review 1 and consultation with public bodies it was agreed, due to paucity of evidence that an appropriateness panel should be the forum for formulation of output on GID. A writers group structured the questions for the survey definition, based on the limited written evidence and added professional experience. A panel of 27 experts in their field were assembled from 5 stakeholder groups including: Gastroenterology, Neurology/Neurodisability, Surgery, Palliative Care and Allied Health Professionals. Geographic representation was from 13 UK specialist centres (including all 4 nations) and 1 centre from Republic of Ireland. The panel rated the appropriateness of definition, investigations and management of GID. A scale of 1–9 enabled scoring of 1–3 to indicate inappropriate, 4–6 uncertain, 7–9 appropriate as criteria for recommendation. Panel agreement index was calculated using a continuous likelihood ratio, with <1 indicated 'general agreement' and >1 'no agreement'. Results were discussed at a moderated. Results: All of the panel completed all questions on 'common' ( table 1 ) and 'uncommon' features of GID. The panel had strong concurrence that GID definition required patients have GMFCS 4–5 cerebral palsy or equivalent and that a temporal relationship between symptoms and enteral feeding had to be present (although this relationship may lessen or cease during progressive disease). Pain, distress, retching, autonomic activation and hypertonicity were seen as common features. Temporal relationship with bowel habit, involuntary movements were considered less common. The diagnosis should be a positive clinical diagnosis (not of exclusion) made by a specialist multi-disciplinary team with experience of feeding disorders in severe neuro-disability. Features suggesting patients feed intolerance has reached the threshold for GID would include malnutrition primarily due to feed cessation and GI symptoms being the greatest burden on QOL for patient/family on appropriate survey. Conclusions: We present a coherent first definition for GID by consensus of a panel of identified experts drawn from 5 invested stakeholder groups. Clear entry point for diagnosing GID will allow for important epidemiological work to report investigations, interventions and outcomes for this complex group of patients. Identifying significant morbidity care burden and mortality in this patient group will help advocate for appropriate health resources, support to carers and families. The ongoing development of a management framework through completion of the RAND 2 process in 2022 should assist navigation of the complex medical and ethical challenges of management of distressing and debilitating symptoms for patients with this condition. Reference: McConnell N, Beattie LM, Richards CA Protheroe S, Barclay AR. JPGN; 2018: 1002 https://www.rand.org/pubs/monograph_reports/MR1269.html Acknowledgement: BSPGHAN BiG funding 2020.